L’eguaglianza di genere riduce la violenza sulle donne? - Bettio, Francesca (Rassegna italiana di sociologia, 2020)
In this article we are concerned with violence against women and gender equality. We ask whether gender equality and violence against women vary in the same direction or whether the former may reduce the latter. We consider violence excluding murder, in particular types of potentially daily violence expressed as physical, sexual and psychological abuse or sexual harassment. Using a fully comparable data source – the 2012 Survey conducted by the Fundamental Rights Agency – we find that gender equality associates with lower levels of intimate partners violence across European countries, while this does not hold for sexual harassment. These findings challenge widely held views in the literature. They are based on a newly developed fuzzy approach to measuring violence against women which accounts for severity and frequency, therefore they correct the distortions in existing analyses that only account for prevalence.